LITERATUR REVIEW TENTANG EFEKTIVITAS TEKNIK HYPNOBIRTHING DALAM MENGURANGI KECEMASAN PERSALINAN - Ariyana, Ariyana (Jurnal Multidisipliner Bharasumba, 2025)
This study aims to review the effectiveness of hypnobirthing techniques in reducing labor anxiety through a systematic literature review. The research methodology used the literature review method by reviewing articles from databases such as PubMed, Scopus, and Google Scholar. The selected articles were published within the time span of 2020 to 2024 and met the inclusion criteria, namely involving pregnant women, publishing relevant results, and using quality research designs. A total of 20 articles were identified and analyzed. The results showed that hypnobirthing significantly reduced anxiety by 35%, shortened the duration of the first stage of labor by 1.5 hours, reduced pain perception by 40%, and decreased the need for medical intervention by 20%. In addition, mothers who used this technique reported higher levels of satisfaction with their labor experience.In conclusion, hypnobirthing is an effective method to improve the birth experience and reduce labor anxiety. Further research with more robust and diverse study designs is needed to strengthen this evidence and understand more about its implementation across different cultural contexts.